Fair re-valuation of wine as an investment - Fabian Y. R. P. Bocart; Christian M. Hafner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
The prices of wine is a key topic for market participants interested in valuing their stock, including dealers, restaurants or consumers who may be interested in optimizing their purchases. As a closely related issue, re-valuation is the need to regularly update the value of a stock. This need is especially met by fund managers in the growing industry of wine as an investment. In this case, fair-value measurement is compulsory by law. We briefly review methods available to funds and introduce a new quantitative method aimed at meeting IFRS 13 compliance for fair valuation. Using auction data, we apply our method to compute current fair value of a basket of wines.
Keywords: C14; C43; M40; G12; 330; IFRS13; hedonic regression; repeated sales; wine investment